IMPLEMENTASI KEBIJAKAN PUBLIK KANTOR PERTANAHAN KABUPATEN PATI ATAS PENGECEKAN SERTIFIKAT TANAH BERBASIS ONLINE - Berliani, Lintang; Antoro, Aji Fajar Suryo (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
Public services are activities carried out by state officials, including the National Land Agency. BPN has one of the policies in providing online certificate checking services by the PPAT/Applicant. However, in terms of implementation, there were obstacles, both technical and non-technical. The purpose of this study was to find out and analyze the implementation of public policy at the Pati District Land Office for checking online-based land rights certificates. This research is a normative-empirical research, with a descriptive-analytic nature by conducting library research and interviewing employees who work at the Pati District Land Office. The result of this study is that checking online certificates is guaranteed to be valid according to Ministerial Regulation ATR BPN No. 5 of 2017, either through the BPN website or the